2019
DOI: 10.1016/j.envint.2019.04.038
|View full text |Cite
|
Sign up to set email alerts
|

Biomonitoring of pesticides, pharmaceuticals and illicit drugs in a freshwater invertebrate to estimate toxic or effect pressure

Abstract: Multiple classes of environmental contaminants have been found in aquatic environments, globally. Understanding internalised concentrations in the organism could further improve the risk assessment process. The present study is concerned with the determination of several contaminant classes (107 compounds) in Gammarus pulex collected from 15 sites covering 5 river catchments across Suffolk, UK. Quantitative method performance was acceptable for 67 compounds including pharmaceuticals, pes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(42 citation statements)
references
References 61 publications
3
39
0
Order By: Relevance
“…However, this direct LC–MS/MS method included several new compounds, most notably biocides, of which only terbutryn was found in London wastewater samples. Recently, fenuron was determined at high frequency in biota and river water in Suffolk, UK by our group, even though it has been removed from use in the UK ( Miller et al, 2019 ). Fenuron was not detected in London wastewater on this occasion.…”
Section: Resultsmentioning
confidence: 99%
“…However, this direct LC–MS/MS method included several new compounds, most notably biocides, of which only terbutryn was found in London wastewater samples. Recently, fenuron was determined at high frequency in biota and river water in Suffolk, UK by our group, even though it has been removed from use in the UK ( Miller et al, 2019 ). Fenuron was not detected in London wastewater on this occasion.…”
Section: Resultsmentioning
confidence: 99%
“…The analytical workflow used for determination of compounds in animal, water and sediment samples followed a previous validated method for G. pulex ( Miller et al., 2019b ). Macroinvertebrate samples were lyophilised at −50 °C under vacuum for 24 h. Pooled samples of organisms were placed into 2 mL Eppendorf tubes with a 3 mm diameter tungsten carbide bead and subsequently ground into a fine powder using a TissueLyser LT (Qiagen, Hilden, Germany) set at 50 Hz for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…Another class of chemicals often present in wastewater (that overlap with pharmaceuticals) are recreational drugs, but these have not had nearly as much focus as environmental contaminants by comparison, likely due to the obvious difficulties for regulation. Our previous study ( Miller et al., 2019b ) showed that several of these compounds were frequently found in surface water and biota which included cocaine, ketamine and 3,4-methylenedioxy methamphetamine (MDMA). These compounds overlap with sewage epidemiology studies that often report their occurrence in wastewater to link to public consumption ( González-Mariño et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, because the VICH guidelines are not applicable to existing veterinary drugs, their environmental impact remains unknown. Thus, little information is available regarding the environmental risks of a majority of veterinary drugs (Eguchi et al, 2004;Fukunaga et al, 2006;Garric et al, 2007;Lútzhøft et al, 1999;Halling-Sørensen, 2000;Yang et al, 2008), and reliable data is desired (Miller et al, 2019).…”
Section: Introductionmentioning
confidence: 99%